Telehealth parent coaching to improve daily living skills for children with ASD. Issue 2 (18th February 2021) - Gerow, Stephanie; Radhakrishnan, Supriya; S. Akers, Jessica; McGinnis, Kristina; Swensson, Remington
Abstract : Children with autism spectrum disorder often display deficits in daily living skills. Behavior analysts can use telehealth, such as videoconferencing technology, to deliver interventions to families of these children. Given the COVID‐19 pandemic and the common barriers to accessing behavioral interventions, it is imperative to evaluate the effectiveness and practicality of delivering behavioral interventions via telehealth. This study evaluated the efficacy of a parent‐implemented intervention with coaching via telehealth to improve daily living skills. Children ranging in age from 5 to 9 years participated in the study with 1 or 2 of their parents serving as the primary implementer(s). Parents implemented the intervention with fidelity and the intervention yielded increases in independent daily living skill completion for all 4 participants.